Background of Parents in Selecting School for Children at Primary School Level - Jannah, Miftakhul; Eko Pramono, Suwito; Utanto, Yuli (Educational Management, 2020)
Education is aimed at improving the quality of human life, both individually and in society. Education is not separated from an institution where learning is a school. There is no denying the quality of service between public and private schools. However, the phenomenon is in contrast to current on-going program of the government to promote qualified and affordable education through public schools. This research aims to analyze background of primary school selection for parents as seen at a private school in Purwokerto. This research uses qualitative method with study case type. The research was conducted at a primary school in Purwokerto. The data sources were obtained from the students’ parents, teachers, and the principal. Techniques of collecting data were observation, comprehensive interview, and document study. The validity test was done by source triangulation. The finding showed that parents considered two factors: theological and academic factors. The theological factor was based on religious consideration. Parents wanted their children to have strong religious foundation. The academic factors dealt with the human resource ability to achieve both academic and non-academic achievements for the students.